Natural Plasmodium falciparum Infection Stimulates Human Antibodies to MSP1 Epitopes Identified in Mice Infection Models upon Non-Natural Modified Peptidomimetic Vaccination - Rodríguez, Zully Johana; Melo, Fredy Leonardo; Torres, Angela; Agrawal, Nikhil; Cortés-Vecino, Jesús Alfredo; Lozano, José Manuel (Molecules (Basel, Switzerland), 2023)
(1) Background: Malaria, a vector-borne infectious disease, is caused by parasites of the Plasmodium genus, responsible for increased extreme morbidity and mortality rates. Despite advances in approved vaccines, full protection has not yet been achieved upon vaccination, thus the development of more potent and safe immuno-stimulating agents for malaria prevention is a goal to be urgently accomplished. We have focused our research on a strategy to identify Plasmodium spp. epitopes by naturally acquired human antibodies and rodent malaria infection models immunized with site-directed non-natural antigens. (2) Methods: Some predictive algorithms and bioinformatics tools resembling different biological environments, such as phagosome-lysosome proteolytic degradation, affinity, and the high frequency of malaria-resistant and -sensitive HLA-II alleles were regarded for the proper selection of epitopes and potential testing. Each epitope’s binding profile to both host cells and HLA-II molecules was considered for such initial screening. (3) Results: Once selected, we define each epitope-peptide to be synthesized in terms of size and hydrophobicity, and introduced peptide-bond surrogates and non-natural amino acids in a site-directed fashion, and then they were produced by solid-phase peptide synthesis. Molecules were then tested by their antigenic and immunogenic properties compared to human sera from Colombian malaria-endemic areas. The antigenicity and protective capacity of each epitope-peptide in a rodent infection model were examined. The ability of vaccinated mice after being challenged with P. berghei ANKA and P. yoelii 17XL to control malaria led to the determination of an immune stimulation involving Th1 and Th1/Th2 mechanisms. In silico molecular dynamics and modeling provided some interactions insights, leading to possible explanations for protection due to immunization. (4) Conclusions: We have found evidence for proposing MSP1-modified epitopes to be considered as neutralizing antibody stimulators that are useful as probes for the detection of Plasmodium parasites, as well as for sub-unit components of a site-directed designed malaria vaccine candidate.